Barriers to the adoption of the ART approach as perceived by dental practitioners in governmental dental clinics, in Tanzania - Emil N. Kikwilu; Jo E. Frencken; Jan Mulder (University of São Paulo, 2009)
OBJECTIVES: This study aimed to determine the magnitude of the barriers to the practice of Atraumatic Restorative Treatment (ART) as perceived by dental practitioners working in pilot dental clinics, and determine the influence of these barriers on the practice of ART. MATERIAL AND METHODS: A validated and tested questionnaire on barriers that may hinder the practice of ART was administered to 20 practitioners working in 13 pilot clinics. Factor analysis was performed to generate barrier factors. These were patient load, management support, cost sharing, ART skills and operator opinion. The pilot clinics kept records of teeth extracted; teeth restored by conventional approach and teeth restored by ART approach. These treatment records were used to compute the percentage of ART restorations to total teeth treated, percentage of ART restorations to total teeth restored and percentage of total restorations to total teeth treated. The mean barrier scores were generated and compared to independent variables, using the t-test. The influence of barriers to ART-related dependent variables was determined using Pearson correlation coefficients. RESULTS: Mean barrier values were low, indicating low influence on ART practice. Female practitioners had higher scores on patient load than male practitioners (p = 0.003). Assistant Dental Officers had higher scores on cost sharing than Dental Therapists (p = 0.024). Practitioners working in urban clinics had higher mean scores on patient load than those who worked in rural clinics (p = 0.0008). All barrier factors were negatively correlated with ART practice indices but all had insignificant association with ART practice indices. CONCLUSION: The barriers studied were of low magnitude, with no significant impact on practice of ART in dental clinics in the pilot area.